2010
DOI: 10.1175/2010jpo4380.1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Structure of Kelvin Waves in the Indonesian Throughflow Exit Passages

Abstract: The subsurface structure of intraseasonal Kelvin waves in two Indonesian Throughflow (ITF) exit passages is observed and characterized using velocity and temperature data from the 2004-06 International Nusantara Stratification and Transport (INSTANT) project. Scatterometer winds are used to characterize forcing, and altimetric sea level anomaly (SLA) data are used to trace the pathways of Kelvin waves east from their generation region in the equatorial Indian Ocean to Sumatra, south along the Indonesian coast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 54 publications
8
87
1
1
Order By: Relevance
“…Furthermore, a normal mode approximation is also applicable to explain the link between the vertical structure of v 0 and stratification. We suggest that these characteristics pertinent to the 2-to 3-month variability [36] The 0 , u 0 , and v 0 data in Lombok Strait also demonstrate two Kelvin wave attributes in the semi-geostrophic balance between v 0 and d 0 /dx and in enhanced d 0 /dx, which corroborates those reported by Drushka et al [2010]. The v 0 data in Lombok Strait and those in Makassar Strait are coherent and yield a Kelvin wave dispersion relationship between the wavenumber and wave frequency.…”
Section: Discussion and Summarysupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, a normal mode approximation is also applicable to explain the link between the vertical structure of v 0 and stratification. We suggest that these characteristics pertinent to the 2-to 3-month variability [36] The 0 , u 0 , and v 0 data in Lombok Strait also demonstrate two Kelvin wave attributes in the semi-geostrophic balance between v 0 and d 0 /dx and in enhanced d 0 /dx, which corroborates those reported by Drushka et al [2010]. The v 0 data in Lombok Strait and those in Makassar Strait are coherent and yield a Kelvin wave dispersion relationship between the wavenumber and wave frequency.…”
Section: Discussion and Summarysupporting
confidence: 84%
“…[37] Drushka et al [2010] Unlike the study of Zhou and Murtugudde [2010], which suggested that the MJO affected the intraseasonal variability only at the ITF outflow passages such as Lombok Strait, we propose that the MJO-related oceanic Kelvin wave is also observed in Makassar Strait.…”
Section: Discussion and Summarycontrasting
confidence: 63%
See 2 more Smart Citations
“…The semiannual signal in ITF transport is much more dominant than previously thought (relative to the annual signal). These Kelvin waves can also occur on intraseasonal timescales in response to Madden Julian Oscillation wind fluctuations and correspondingly drive transport, thermocline, and temperature anomalies in the ITF exit passages (Drushka et al, 2010) and up into Makassar Strait (Pujiana et al, 2010). During the northwest monsoon of November-January, the surface transport relaxes in Timor Strait and weakly reverses in Ombai, Lombok, and Makassar Strait, so the main core of the ITF is subsurface.…”
Section: Indonesian Throughflowmentioning
confidence: 99%